THE INFLUENCE OF CR, ROA, AND ROE ON SHARE PRICES IN COMPANIES LISTED ON THE LQ45 INDEX - Nengsih, Titin Agustin; Saputra, Catur Ragil; Mareli, Adelia; As’ad, As’ad; Suhar, Suhar; Rafidah, Rafidah; Rosmanidar, Elyanti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to investigate the influence of the Current Ratio, Return on Assets, and Return on Equity on stock prices. The population in this research are companies listed on the LQ45 Index for the 2022 period. The method in this research uses a quantitative approach. The sampling technique uses a purposive sampling technique, namely a sampling technique based on certain criteria. The number of samples in this research was 16 companies. The data analysis method uses descriptive statistics and multiple regression analysis. Based on the results of this research, it shows that partially the Current Ratio has no effect on stock prices, Return on Assets has an impact on stock prices, and Return on Equity has no effect on stock prices.